Dynamic housing expenditures and household welfare - Laura Blow; Lars Nesheim (Centre for Microdata Methods and Practice (cemmap), 2009)
In this paper we develop a measure of current expenditures on housing services for owner-occupiers. Having such a measure is important for measuring the relative welfare of households, especially when comparing renters and owners and for measuring inflation. From a theoretical perspective expenditures equal the shadow price of housing services (the marginal rate of substitution between housing services and non-durable consumption) multiplied by the quantity of housing services consumed. In an idealised world, two simple measures of the shadow price are available; the user cost of housing capital and the rental price of an equivalent rental house. However, imperfect capital markets, risk aversion, the tax system, moving costs and systematic differences between houses available in the rental and owner occupied sectors drive a wedge between the shadow price of housing and these other two measures. This paper contributes to previous research by calibrating a lifecycle model of housing investment and consumption to data from the UK Family Expenditure Survey and by developing measures of the shadow price of housing that take into account uncertainty in house prices, interest rates and incomes, dynamic life cycle choices, and liquidity constraints that depend on both income and house value.
Keywords: C88; D12; E21; R21; 330; shadow price; housing; liquidity constraints; lifeycle models; Wohneigentum; Wohnkosten; Opportunitätskosten; Konsumentenverhalten; Lebenszyklus; Großbritannien